2016
DOI: 10.1016/j.kint.2016.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Repression of CMIP transcription by WT1 is relevant to podocyte health

Abstract: The WT1 (Wilm's tumor suppressor) gene is expressed throughout life in podocytes and is essential for the functional integrity of the glomerular filtration barrier. We have previously shown that CMIP (C-Maf inducing protein) is overproduced in podocyte diseases and alters intracellular signaling. Here we isolated the proximal region of the human CMIP promoter and showed by chromatin immunoprecipitation assays and electrophoretic-mobility shift that Wilm's tumor protein (WT1) bound to 2 WT1 response elements, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 58 publications
(86 reference statements)
1
11
0
Order By: Relevance
“…Details of the construction of Cmip lox/lox mice have been previously reported. 17 A triple transgenic mouse strain (CD2-rtTA/TetOn-Cre/CMIP loxP/loxP ) was generated by sequential crossing. We first crossed Cmip lox/lox mice with C.Cg-Tg(tetO-cre)1Jaw/J mice (strain N° 006244) that were purchased from Jackson laboratory (Bar Harbor, ME USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the construction of Cmip lox/lox mice have been previously reported. 17 A triple transgenic mouse strain (CD2-rtTA/TetOn-Cre/CMIP loxP/loxP ) was generated by sequential crossing. We first crossed Cmip lox/lox mice with C.Cg-Tg(tetO-cre)1Jaw/J mice (strain N° 006244) that were purchased from Jackson laboratory (Bar Harbor, ME USA).…”
Section: Methodsmentioning
confidence: 99%
“… 15 However, CMIP is scarcely detectable at both the transcript and protein levels in adult tissues under physiological conditions, which is due at least in part to its notable transcriptional repression by NF-kB and WT1, two master transcription factors. 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
“…CMIP (Cmaf-inducing protein) is a recently identified gene that encodes an 86 kDa protein. In physiological situations, CMIP is repressed by both WT1 and NF-kB, two major transcription factors in podocytes, which may account for its low levels or non-detection in normal glomeruli [ 9 , 10 ]. Evidence based on in vitro and in vivo studies suggest that CMIP induces podocyte signaling disorders and inhibits remodeling of cytoskeleton contributing to podocyte damages [ 11 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The short protein isoform contributes to several biological pathways and the function of the long protein isoform is rarely known. Several reports have demonstrated that CMIP participates in human kidney diseases through regulating behaviors of podocytes [8, 12, 13]. CMIP is also reported to be associated with reading-related behaviors [14, 15], short-term memory, and language-related traits [7, 16].…”
Section: Introductionmentioning
confidence: 99%